Association of polymorphisms in the MyD88, IRAK4 and TRAF6 genes and susceptibility to type 2 diabetes mellitus and diabetic nephropathy in a southern Han Chinese population. (5th July 2016) - Guo, Congcong; Zhang, Liju; Nie, Lihong; Zhang, Na; Xiao, Di; Ye, Xingguang; Ou, Meiling; Liu, Yang; Zhang, Baohuan; Wang, Man; Lin, Hansheng; Yang, Guang; et al.
Abstract: Type 2 diabetes mellitus (T2DM) has been linked to a state of low-grade inflammation resulting from abnormalities in the innate immune pathway. MyD88 is an essential adaptor protein for TLR signaling, which is involved in activating NF-κB through IRAK4 and TRAF6. To investigate the effects of the MyD88, IRAK4 and TRAF6 polymorphisms in the susceptibility of T2DM and diabetic vascular complications, eight SNPs were analyzed in 553 T2DM patients and 553 matched healthy controls. Gene-gene interactions and haplotype associations were also evaluated. We found a significant increased risk of T2DM for the AG genotype of rs6853 in MyD88 gene and the CT genotype of rs4251532 in IRAK4 gene. Significant association was also found between rs16928973 in TRAF6 gene and diabetic nephropathy (DN) under the allelic model. Moreover, the TA haplotype in TRAF6 was negatively associated with DN. No significant gene-gene interactions were found. In conclusion, our results indicate that the polymorphisms in TLR-MyD88-NF-κB signaling pathway confer genetic susceptibility to T2DM and DN. Highlights: This was the first association study between SNPs in MyD88, IRAK4 and TRAF6 genes with T2DM and its complications. The AG genotype of rs6853 and the CT genotype of rs4251532 were positively associated with T2DM risk. The minor allele T of rs16928973 and TA haplotype in TRAF6 were negatively associated with diabetic nephropathy risk. No significant gene-gene interactions were found.